Pengaruh Customer Value Terhadap Customer Loyalty Pengguna Fitur Go-Food Pada Aplikasi Go-Jek - Rachman, Arief Syaiful; Pamungkas, Wisnu Bayu; Yusuf, Abdul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the extent of The Influence of customer value on customer loyalty users of go-food features in the go-jek application. The location of this research is in Karawang, West Java. The population is all users of the Go-Food feature. The sample is some 100 users of the Go-Food feature, the sampling technique uses the google form. Data analysis using SPSS which has been tested for validity and reliability. The results of this study state that customer value has a positive and significant influence on customer loyalty of Go-Food feature users in Indonesia.